2022
DOI: 10.1186/s12880-022-00895-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of aortic valve regurgitation in 4D flow cardiac magnetic resonance: at which level should we measure?

Abstract: Purpose To find the best level to measure aortic flow for quantification of aortic regurgitation (AR) in 4D flow CMR. Methods In 27 congenital heart disease patients with AR (67% male, 31 ± 16 years) two blinded observers measured antegrade, retrograde, net aortic flow volumes and regurgitant fractions at 6 levels in 4D flow: (1) below the aortic valve (AV), (2) at the AV, (3) at the aortic sinus, (4) at the sinotubular junction, (5) at the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Contrary to those results, other groups reported that 4 D flow MRI significantly underestimates systolic peak flow velocities, while 2 D flow MRI gives accurate results [18,19]. Other groups found significant underestimation of aortic or pulmonary regurgitation and intracardiac flow when using 4 D flow MRI measurements [20][21][22]. It is not clear if those differences occur when using sequences and scanners from different vendors or if there are other explanations.…”
Section: Discussionmentioning
confidence: 80%
“…Contrary to those results, other groups reported that 4 D flow MRI significantly underestimates systolic peak flow velocities, while 2 D flow MRI gives accurate results [18,19]. Other groups found significant underestimation of aortic or pulmonary regurgitation and intracardiac flow when using 4 D flow MRI measurements [20][21][22]. It is not clear if those differences occur when using sequences and scanners from different vendors or if there are other explanations.…”
Section: Discussionmentioning
confidence: 80%
“…It is important to note that the best reproducibility was obtained using the sinotubular junction as the anatomical landmark. Four-dimensional flow MRI has potential advantages over phase-contrast MRI; nonetheless, further studies are needed to optimize its clinical use in AR quantification [40] (Figure 1). In summary, the most reliable approach for assessing the severity of AR is to incorporate different Doppler methods [13].…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%